Enabling Low-Carbon Tourism Through Technology Transfer in Indonesia: A PESTEL Analysis - Angga Wijaya Holman Fasa; Mahardhika Berliandaldo; Muhammad Iqbal Rosyidi; Raditya Raditya (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
The tourism and travel sector has contributed significantly to Indonesia’s economic growth and robust development. Despite its positive impact, tourism and travel business activities also potentially impact environmental loss. In order to reduce these negative impacts, the new concept of tourism, namely low-carbon tourism, which focuses on environmental sustainability, can be implemented as the enabler. One of the factors that can support the implementation is the existence of environmentally friendly technology that requires a technology transfer process. This paper aims to overview the role and implication of technology transfer for enabling low-carbon tourism in Indonesia and outlining a conceptual framework for addressing the political (P), economic (E), social (S), technological (T), environmental (E), and legal (L) factors that constrain and support in enabling low-carbon tourism through technology transfer in Indonesia. A qualitative library research method and PESTEL analysis were employed to analyze and map the implications of external factors influencing the development of low-carbon tourism through technology transfer in Indonesia. The paper denotes that all the factors (political, economic, social, technological, environmental, and legal) were interrelated. Nevertheless, the economic factor was the only one with a moderate policy to encourage businesses to use green practices, particularly for the carbon tax policy. Consequently, there was still an opportunity for monetary policy to promote low-carbon tourism.